(untitled) (Research, Society and Development, 2022)
Nursing management requires a greater emphasis from nurses on leadership, coordination and direction skills, such capabilities make professionals seek greater knowledge, making it possible to respond to professional, organizational and personal demands. Therefore, the objective of this study was to identify in the national bibliography the competences of nurses in the managerial aspect in the hospital environment. Methodologically, this is a narrative review, carried out through the virtual databases PubMed, Scielo and Lilacs. Data collection took place in 2020/1 and 2020/2. For the construction of the following research, 10 articles were selected, where their results and discussions were presented. From the perspective of nurses working in the hospital context, the managerial competencies of leadership, decision making, communication and planning and organization are essential to their performance. Nurses understand their importance in this role in the institution, perceiving themselves as aggregating professional and knowledgeable of labor and administrative relationships, proposing strategies capable of achieving planned and quality care to several clients, striving for critical thinking, professional satisfaction, recognition and quality of care, elements inherent to the achievement and satisfaction of a craftsman. It is evident in educational measures, the formation of support groups, interventions and nursing consultations as educational actions developed by nursing, as well as providing subsidies for studies in the area and academic support regarding the topic addressed.